ESTABLISHMENT OF REGIONAL REGULATIONS AS AN EFFORT TO PROTECT FOLKLORE IN BOJONEGORO REGENCY - Ida Wahyuliana; Aprilina Pawestri; Helmy Boemiya; Banu Prasetyo; Wella Mareta Nanda (Universitas Trunodjoyo Madura, 2024)
Folklore is a collection of traditional creations made by groups or individuals in society that show their social and cultural identity based on standards and values spoken or followed from generation to generation. Bojonegoro Regency has folklore, including the Bojonegoro Langen Tayub Dance, Thengul Wayang, and Jonegoroan Batik Art. Folklore in Bojonegoro Regency needs to be protected. One way to do this is by establishing the Bojonegoro Regency Regional Regulation. Internal and external obstacles will undoubtedly be encountered in forming the Bojonegoro Regency Regional Regulation. This study aims to determine the reasons for the need to create a Regional Regulation that regulates folklore in Bojonegoro Regency and to choose the obstacles encountered in the formation of the Bojonegoro Regency Regional Regulation that regulates folklore. The research method used is empirical juridical because it first examines secondary and primary data in the field. The research specification used is analytical descriptive. Namely, the data obtained is collected, arranged, explained, and analyzed. The results of this study conclude that the Formation of Regional Regulations of Bojonegoro Regency needs to be carried out for the following reasons: (a). Folklore in Bojonegoro Regency has economic value (b). Folklore in Bojonegoro Regency is the identity and icon of the Bojonegoro Regency area (c). to maintain the existence of folklore in Bojonegoro Regency. The obstacles encountered are internal as follows: (a). The high cost and extended period in forming Regional Regulations, (b). Lack of socialization in the community (c) Lack of community participation (d). The difficulty of inventorying folklore in Bojonegoro Regency. External obstacles are in evaluating the formation of Regional Regulations from the East Java Provincial Government, which will take quite a long time.